Gendered eviction, protest and recovery: a feminist political ecology engagement with land grabbing in rural Cambodia. Issue 6 (2nd November 2017) - Lamb, Vanessa; Schoenberger, Laura; Middleton, Carl; Un, Borin
Abstract : We examine what we argue has been overlooked in the Cambodian context: the roles and practices of women in relation to men and their complementary struggles to protest land grabbing and eviction, and subsequently rebuild community and state relations. We present research carried out in Cambodia in 2014–2015 in Kratie, the country's most concessioned province. Through a feminist political ecology lens, we examine how protest and post-eviction community governance are defined as women's or men's work. Our case also reveals how 'rebuilding' gender relations in rural Cambodia simultaneously rebuilds uneven community and state relations.